1997
DOI: 10.1089/hum.1997.8.17-2057
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficiency and Safety of a Second-Generation Replication-Conditional HSV1 Vector for Brain Tumor Gene Therapy

Abstract: A second-generation replication-conditional herpes simplex virus type 1 (HSV) vector defective for both ribonucleotide reductase (RR) and the neurovirulence factor gamma34.5 was generated and tested for therapeutic safety and efficiency in two different experimental brain tumor models. In culture, cytotoxic activity of this double mutant HSV vector, MGH-1, for 9L gliosarcoma cells was similar to that of the HSV mutant, R3616, which is defective only for gamma34.5, but was significantly weaker than that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
107
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 17 publications
2
107
0
1
Order By: Relevance
“…into BALB /c mice. Kramm et al 8 independently reported a second virus also defective for 34.5 and RR. Although both of these viruses appeared to have increased safety compared to hrR3, the additional mutation decreased therapeutic efficacy, presumably because of its very poor growth characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…into BALB /c mice. Kramm et al 8 independently reported a second virus also defective for 34.5 and RR. Although both of these viruses appeared to have increased safety compared to hrR3, the additional mutation decreased therapeutic efficacy, presumably because of its very poor growth characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Mutants containing deletions in two viral genes have been developed for potential use against malignant brain tumors by two groups 8,9 to further increase safety by altering multiple mechanisms of virulence. Both viruses have a deletion in the neurovirulence gene 34.5 and in the ICP6 gene, which encodes for the large subunit of the HSV-1 ribonucleotide reductase ( RR ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 A difficulty in evaluating the efficacy of replication-competent HSV-1 in vivo has been the lack of suitable immunocompetent animal tumor models due to the relative resistance of rodent cells to HSV-1 infection. The 9L rat gliosarcoma model has been used for replication-competent HSV studies 36,45,46 as well as HSV-tk/GCV therapy, [5][6][7]10,11,14 but the cell line is highly resistant to HSV-1, 36 especially G207 (our unpublished data), and is immunogenic; 58 therefore, it is not suitable for G207 studies. A/J is one of the most sensitive mouse strains to HSV-1 infection, 49 and syngeneic N18 tumors in A/J mice are very responsive to G207 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…MGH-1, a multimutated HSV-1 vector with the same mutation as G207, exhibited no therapeutic effect in the 9L tumor model with or without GCV administration. 36 The resistance of 9L cells to MGH-1 seemed to largely account for the lack of efficacy. It has also been shown that enhancement of the effect of GCV on hrR3-mediated killing was observed only in 9L cells, and not in various human colorectal cancer cells in culture or in nude mice.…”
Section: Discussionmentioning
confidence: 99%